Innovation of sample preparation cabinets for bacterial culture work - Weerakul, Jetana; Boukum, Supon; อุ่นสิม ธนันชนัย (Kalasin University Journal of Science Technology and Innovation, 2024)
The purposes of the research were to 1) Invent a sample preparation cabinet for bacterial culture work and to 2) Study performance testing of sample preparation cabinets for bacterial culture work. The research findings showed the 1) Invention of the vertical flow bacterial culture preparation. The size of the cabinet is 60 x 90 x 70 centimeters the material is made from 8millimeter thick Formica laminated plywood. The front has a glass cover with 5millimeter thick to protect from dust and ultraviolet light (UV). The top has a fan system that filters air from outside through a 12-inch HEPA Filter. Inside there is a lighting system with an 18-watt fluorescent light bulb and a PHILIPS UV T8 TUV 18W bulb (F17T8) for disinfecting the cabinet. There is a device to display temperature and humidity while working. The system of fans, lighting, disinfection lamps is controlled by switch box outside the cabinet. 2) The results of the sterility study showed that the cabinet could hold up to 35 agar plates with a diameter of 110 millimeter. It was found that all the agar plates prepared in the cabinet were sterile. 3) Results of sample preparation in the cabinet showed the growth the Salmonella typhimurium (TA 100). Comparing between the invented cabinets and Standard Laminar Air Flow Cabinet. It was found that the two cabinets gave the same results in terms of appearance and number of colonies, both as a result of the negative control and as a result of the positive control. The number of negative control colonies in both cabinet and each plate did not exceed 100 , the number of colonies from plates prepared with standard cabinets counted an average of 47.66 ± 15.85 colonies and plates from the artificial cabinets counted an average of 52.44 ± 17.61 colonies and p-value = 0.25 , the number of positive control colonies counted more than 600 colonies on every plate.